Factors Influence the Event of Stunting on Toddlers in the Working Area of Puskemas Tarus in Kupang Regency - Maria Margarini Leki; Deviarbi Sakke Tira; Sigit Purnawan (Universitas Nusa Cendana, 2022)
Stunting is a condition of chronic malnutrition that occurs from growth and development starting from the fetal period. Many children under five are stunted due to malnutrition, and many toddlers are often sick. This study aimed to determine the factors influencing the incidence of stunting in toddlers. This research was conducted in the Work Area of ​​the Tarus Health Center, Central Kupang District, Kupang Regency, and was carried out from May 2021. The research method used was an analytical survey using a case-control design. The samples taken were 66 children under five, namely 33 under five in the case group and 33 in the control group. Data analysis used the Chi-Square. The results showed that the variables related to the incidence of stunting were LBW history (p= 0.001, OR= 6.250, 95%CI= 2.131-18.330), history of infectious diseases (p= 0.000, OR= 8.543, 95%CI=2.796-26.104), and feeding patterns (p= 0.000, OR= 8.333, 95%CI= 2.760-25.157). Meanwhile, exclusive breastfeeding history and mother's knowledge level were not related to the incidence of stunting (p= 0.325, p= 0.453, consecutively). Parents should consider the diversity of consumption patterns in children under five to prevent stunting.